Building a model of the goods delivery system that uses unmanned aerial vehicles based on priority - Knysh, Bogdan; Kulyk, Yaroslav (Eastern-European Journal of Enterprise Technologies, 2023)
This paper considers the organization of a goods delivery process, which is selected as the study object. It has been established that the main problems that arise in this case can be caused, for example, by the imperfection of infrastructure and transport for delivery. This can be partially solved through the use of unmanned aerial vehicles for the delivery of goods, as well as by solving tasks related to effective control over their movement. However, there is another issue associated with the insufficient efficiency of existing mathematical models of goods delivery systems involving unmanned aerial vehicles since the maximum possible delivery speed is not provided. Therefore, there is a need to find a better solution to this problem. A model of the goods delivery system that uses unmanned aerial vehicles based on priority has been built. The resulting model takes into account the intensity of requests and provides a shorter waiting time in the queue, and therefore a greater delivery speed. Models of single-channel and multichannel goods delivery systems with failures and expectations were investigated according to probability. It was found that the devised goods delivery system is on average less loaded per unit of time and makes it possible to serve more orders while incoming orders are in line for less time. The same models have also been investigated according to the waiting time in the queue. It has been established that the devised goods delivery system provides a shorter waiting time in the queue. At the same time, the deviation between the theoretical and experimental values of probabilities and waiting time is 2 % and 3 %, respectively, which allows us to assert high accuracy of the results and the devised model as a whole. The results reported here could be used in practice in the absence of an extensive network of logistics and sales and remoteness of recipients